2020
DOI: 10.1186/s12893-020-00700-3
|View full text |Cite
|
Sign up to set email alerts
|

Total resuscitative endovascular balloon occlusion of the aorta causes inflammatory activation and organ damage within 30 minutes of occlusion in normovolemic pigs

Abstract: Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) causes physiological, metabolic, end-organ and inflammatory changes that need to be addressed for better management of severely injured patients. The aim of this study was to investigate occlusion time-dependent metabolic, end-organ and inflammatory effects of total REBOA in Zone I in a normovolemic animal model. Methods: Twenty-four pigs (25-35 kg) were randomized to total occlusion REBOA in Zone I for either 15, 30, 60 min (REBOA15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Since c-REBOA prevents blood supply to the SMA, the organs supplied by this artery are compromised and can undergo irreversible cell injury. The repercussion of this is duodenal necrosis, as previously discussed, in addition to the elevation of pancreatic enzymes, as described by Sadeghi et al [10]. Other tissues and organs that have been reportedly affected are skeletal muscle, kidneys, and the liver, which was reported in Sadeghi et al's study with 24 swine ( Table 2) [10].…”
Section: Metabolic Effectsmentioning
confidence: 62%
See 3 more Smart Citations
“…Since c-REBOA prevents blood supply to the SMA, the organs supplied by this artery are compromised and can undergo irreversible cell injury. The repercussion of this is duodenal necrosis, as previously discussed, in addition to the elevation of pancreatic enzymes, as described by Sadeghi et al [10]. Other tissues and organs that have been reportedly affected are skeletal muscle, kidneys, and the liver, which was reported in Sadeghi et al's study with 24 swine ( Table 2) [10].…”
Section: Metabolic Effectsmentioning
confidence: 62%
“…The repercussion of this is duodenal necrosis, as previously discussed, in addition to the elevation of pancreatic enzymes, as described by Sadeghi et al [10]. Other tissues and organs that have been reportedly affected are skeletal muscle, kidneys, and the liver, which was reported in Sadeghi et al's study with 24 swine ( Table 2) [10]. These abnormalities were either not seen or seen only to a lesser degree in a partial occlusion compared to complete occlusion.…”
Section: Metabolic Effectsmentioning
confidence: 64%
See 2 more Smart Citations
“…In a separate study conducted by Sadeghi et al, severe intestinal damage was reported in two of three groups of swine undergoing REBOA separated by duration of inflation. Both the 30-min and 60-min groups showed damage not seen in the 15-min group [ 89 ].…”
Section: Introductionmentioning
confidence: 99%